LANGUE DES JEUNES: THE USE OF GREETINGS BY E-SPORTS PLAYERS - Aveny Septi Astriani; Lazuardy Akbar Fauzan; Yusuf Al-Arief (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2022)
One of the media used by teenagers to greet each other is electronic sports. Through e-sports, teenagers wave greetings and express their thoughts in words or sentences. The greeting is closely related to the name and designation used to address people. This qualitative descriptive study discusses e-sports players' greetings, especially those on the E-sport Podcast YouTube channel. The data were collected from five transcribed videos by note-taking. Then, they were analyzed using the theory of greeting according to the theory of Crystal (1997) and Kridalaksana (1980). Finally, the data were presented in tabulation for easy understanding. Based on the data analysis, the greetings used by e-sport players include personal names, pronouns, other nouns, kinship, and other words to show annoyance or anger.